Structural Performance Assessment Based on Statistical and Wavelet Analysis of Acceleration Measurements of a Building during an Earthquake - Mosbeh R. Kaloop; Jong Wan Hu; Mohamed A. Sayed; Jiyoung Seong (Shock and Vibration)
This study introduces the analysis of structural health monitoring (SHM) system based on acceleration measurements during an earthquake. The SHM system is applied to assess the performance investigation of the administration building in Seoul National University of Education, South Korea. The statistical and wavelet analysis methods are applied to investigate and assess the performance of the building during an earthquake shaking which took place on March 31, 2014. The results indicate that (1) the acceleration, displacement, and torsional responses of the roof recording point on the top floor of the building are more dominant in the X direction; (2) the rotation of the building has occurred at the base recording point; (3) 95% of the energy content of the building response is shown in the dominant frequency range (6.25–25 Hz); (4) the wavelet spectrum illustrates that the roof vibration is more obvious and dominant during the shaking; and (5) the wavelet spectrum reveals the elasticity responses of the structure during the earthquake shaking.